Visualizing chaperone-assisted protein folding - Horowitz, Scott (Nat Struct Mol Biol, 2016)
Challenges in determining the structures of heterogeneous and dynamic protein complexes have greatly hampered past efforts to obtain a mechanistic understanding of many important biological processes. One such process is chaperone-assisted protein folding, where obtaining structural ensembles of chaperone:substrate complexes would ultimately reveal how chaperones help proteins fold into their native state. To address this problem, we devised a novel structural biology approach based on X-ray crystallography, termed Residual Electron and Anomalous Density (READ). READ enabled us to visualize even sparsely populated conformations of the substrate protein immunity protein 7 (Im7) in complex with the E. coli chaperone Spy. This study resulted in a series of snapshots depicting the various folding states of Im7 while bound to Spy. The ensemble shows that Spy-associated Im7 samples conformations ranging from unfolded to partially folded and native-like states, and reveals how a substrate can explore its folding landscape while bound to a chaperone.